Simplicity as an Artistic Strategy: An Analysis of Sapardi Djoko Damono's Poem “Aku Ingin” in the Perspective of Russian Formalism - Khofifah Indah Baitul Jannah; Atika Rosiana Widarwati; Yusro Edy Nugroho (Journal of Social Science, 2026)
This research aims to prove that the simplicity in the poem "Aku Ingin" by Sapardi Djoko Damono is not just an aesthetic choice, but an artistic strategy that is consciously and systematically designed. The study was conducted using the Russian Formalism approach which places the internal structure of the text as the center of the analysis, regardless of the biographical or social context of the author. With qualitative descriptive methods and close reading techniques, this study identifies the way formal devices work including repetition, defamiliarization, natural metaphors, typography, diction, and stanza symmetry in building poetry literariness. The results of the analysis show that simplicity is built through a number of devices that support each other: the repetition of the phrase "I want to love you simply" as the dominant device that creates parallel rhythms and binds the structure between verses; defamiliarization through the metaphors of "wood to fire" and "cloud to rain" that present love from a new point of view; as well as lowercase typography and the absence of punctuation that reinforce the subtle and contemplative impression. This organized structural simplicity is the dominant element that drives the entire aesthetic system of poetry. This research confirms that Russian Formalism is able to uncover how simplicity works not as a limitation, but as an artistic force that produces a profound aesthetic experience.